MANAJEMEN SARANA DAN PRASARANA PENDIDIKAN DALAM PRESFEKTIF TAFSIR AL-QUR’AN DAN HADIST - Salma Tiaz; Sri Andini; Rokhayani Yuslida Hanum Harahap; Amri Jamil Tanjung; Muhammad Fitriyadi (TARBIYA ISLAMIA : Jurnal Pendidikan dan Keislaman, 2026)
This article aims to analyze the concept of educational facilities and infrastructure management from the perspective of Qur’anic exegesis and hadith. The study employs a library research method using a qualitative descriptive approach. Data were obtained from Qur’anic verses, hadith, exegetical works, and literature relevant to Islamic educational management. The results of the study indicate that the principles of educational facilities and infrastructure management have a strong foundation in Islamic teachings. Planning is reflected in QS. Al-Hasyr (59): 18, which emphasizes the importance of thorough preparation; organization is reflected in QS. An-Nahl (16): 68–69, which demonstrates purposeful management according to function; while supervision is reflected in QS. Al-Mujaadillah (58): 6, which teaches the importance of accountability for every activity. Furthermore, the hadith of the Prophet Muhammad (peace be upon him) highlights the importance of utilizing facilities to support the educational process. Thus, the management of educational facilities and infrastructure in Islam is not merely technical but also embodies the values of trust, responsibility, and accountability.